Gambaran Hematologi Darah Pasca Vaksinasi Porcine Reproductive and Respiratory Syndrome (PRRS) pada Ternak Babi di Kabupaten Kupang - Sole, Marsyella Gloria; Simarmata, Yohanes T. R. M. R.; Gelolodo, Maria Aega (JURNAL KAJIAN VETERINER, 2024)
The potential for expanding pig farming, particularly with native pigs, in East Nusa Tenggara (NTT) Province is significant due to the predominant non-Muslim population in NTT who utilise pigs in traditional and religious ceremonies. However, the high number of pigs in Kupang Regency and conventional farming practices can elevate the likelihood of infections like Porcine Reproductive and Respiratory Syndrome, known as PRRS. Porcine reproductive and respiratory syndrome (PRRS), caused by the PRRS virus (PRRSV), is a significant disease in the pig farming sector. The porcine reproductive and respiratory syndrome virus is highly contagious within pig herds. It can spread through direct contact or contaminated aerosols. Vaccines have been used to limit the disease’s transmission, despite often being considered ineffective. This study analyses the variations in blood haematological parameters before and after PRRS immunisation, including RBC, HGB, PCV, MCV, MCH, MCHC, and WBC. Fifteen pigs were included in the sample. Sampling was conducted two times from the same pigs: before PRRS vaccination and one month post-immunization. SPSS was used for the data analysis. A statistical study using SPSS showed no significant difference in blood hematology following the PRRS vaccination.